Technological Trends In Digital And Interactive Media For Heritage Design: A Systematic Literature Review - Yvier, Eizaveta; Eizstvkov, Tsokur (University of Science and Computer Technology, 2025)
The rapid evolution of digital and interactive media has transformed approaches to heritage design, enabling new ways to preserve, interpret, and engage with cultural assets. This study systematically reviews technological trends in digital and interactive media that support heritage design, emphasizing their implications for graphic design, digital humanities, and cultural communication. A systematic literature review (SLR) was conducted following PRISMA guidelines, supported by PICOS and SPIDER frameworks to ensure methodological rigor and transparency. Relevant studies were retrieved from leading academic databases, including Scopus, Web of Science, and IEEE Xplore, with inclusion and exclusion criteria based on publication type, relevance, and thematic alignment. An initial pool of 87 records was identified, from which 40 studies were finally included after applying quality and eligibility screening. The synthesis identifies five dominant technological directions: immersive technologies (virtual and augmented reality), interactive installations, gamification, artificial intelligence-driven visualization, and participatory digital platforms. These approaches illustrate how heritage design is evolving from static documentation toward dynamic, user-centered, and interdisciplinary experiences. The findings also highlight challenges in accessibility, cultural sensitivity, and sustainable technological integration. Compared with previous reviews in digital heritage and media studies, this work contributes a more design-centered perspective by mapping the convergence between interactive engagement and computational innovation. The study’s novelty lies in its interdisciplinary synthesis that connects visual communication theory with technological practices, offering a conceptual foundation for future research in digital heritage design. Overall, this review clarifies current research trajectories, identifies underexplored gaps, and proposes directions for advancing inclusive and culturally responsive design strategies.